The association of the perioperative neutrophil-to-lymphocyte ratio with wound healing in patients with Wagner grade 3 and 4 diabetic foot ulcers after tibial cortex transverse transport surgery: a prospective observational cohort study - Zhao, Sichun; Guo, Fudie; Zang, Yonghui; Hu, Rong; Yu, Xianjun; Zhang, Hongmei; Xie, Tingting; Li, Xiaoya; Bai, Chunxia; Shi, Haoran; Zhang, Dingwei (Frontiers in Endocrinology, 2024)
Background: Diabetic foot ulcers (DFUs) are severe complications of diabetes, involving multiple etiological factors including neuropathy, vascular insufficiency, and impaired wound healing. The global burden of DFUs is substantial, with significant morbidity and high management costs. Recent advancements have introduced the Tibial Cortex Transverse Transport (TTT) technique, which has shown promising results in the management of severe DFUs by promoting angiogenesis and immunomodulation. Methods: This prospective cohort study enrolled patients with Wagner grade 3 and 4 DFUs, treated using the TTT technique from May 2022 to September 2023 at MianYang Central Hospital. The study assessed the influence of TTT on the perioperative neutrophil-tolymphocyte ratio (NLR), an established biomarker of systemic inflammation, and its correlation with wound healing outcomes. Results: A total of 82 patients were enrolled, with 66 completing the study. The survival analysis revealed that patients with a lower preoperative NLR experienced significantly faster wound healing compared with a high NLR (log rank test P < 0.05; hazard ratio (HR)=0.46; 95% CI: 0.26-0.83). The optimal NLR cut-off values (4.25) were established for predicting wound healing times for DFUs. The median NLR was significantly different before TTT surgery, 3-days after TTT surgery and 1 month after TTT surgery (P＜0.05). Conclusion: TTT technique significantly influences the perioperative NLR and is associated with improved wound healing in DFU patients. The perioperative NLR serves as an effective predictive biomarker for wound healing outcomes, highlighting the significance of interventions targeting NLR values in perioperative management strategies and postoperative monitoring protocols for the treatment of diabetic foot ulcers (DFUs) in clinical practice.